Cotton Based Fragrance Packet for Well-being Applications - BASAK, S.; SAXENA, S.; RAJA, A. S. M.; PATIL, P. G.; KRISHNAPRASAD, G.; NARKAR, R. S.; KAMBLI, N. D. (Cotton Research Journal, 2021)
A well-being fragrance packet based on cellulosic fibres has been developed. This pack contains three layers of cotton nonwoven (100 gram per square meter) as core material. Optimized quantity of natural essential oil (citronella oil) based fragrance has been incorporated in the middle non-woven layer of the cotton. Paper sheet having 2000mL/min permeability has been used as sheath material. Volatile active species of the essential oil infused in the cotton non-woven, slowly diffuse through the upper and lower non-woven layers in the surrounding atmosphere through the pores of the paper sheath material. As per feedback from users, fragrance released from the packet is satisfactory up to seven days in the 25-30 square feet area. Aroma released from the packet was also found to repel mosquitoes. Standard cone test showed that the smell release from the pack was sufficient to repel mosquitoes (100%) up to five days after opening the pack.